PENGARUH MUTASI DAN PROMOSI TERHADAP PRESTASI KERJA GURU SMA NEGERI DI SRAGEN - Vica Stevani, SL Triyaningsih & Sunarso (Universitas Slamet Riyadi, 2016)
SMA negeri is a school organized by the government. The problem in this study is whether there is a significant effect of mutations and promotion of teachers' job performance. The purpose of this study was to determine the significance of the effect of mutations and promotion of teachers' job performance. The usefulness of this research into consideration the delivery of policy to make transfer and promotion that was given to the teachers in order to improve performance. This study uses a survey of high school teachers of State in Sragen. Data that is needed is a general overview, organizational structure, respondents about transfer, promotion and achievement of learning, and the number of teachers from SMA 1, SMA 2 and SMA 3 in Sragen. Sources of data in the form of primary data and secondary data. Data collection techniques with surveys and questionnaires. The sampling technique using simple random sampling of 30 respondents. Data were analyzed using multiple linear regression analysis, t-test, F and coefficient of determination. The results obtained by analysis that there is no significant effect on the performance of a mutation, but there is a significant effect on the promotion of work achievement. The calculation result obtained determination coefficient R2 = 0,748, meaning that 74,80% of job performance is affected by the mutation, and promotions.Keywords: transfer, promotion, job performance